2016 IEEE International Solid-State Circuits Conference (ISSCC) 2016
DOI: 10.1109/isscc.2016.7417962
|View full text |Cite
|
Sign up to set email alerts
|

9.5 A dual-band digital-WiFi 802.11a/b/g/n transmitter SoC with digital I/Q combining and diamond profile mapping for compact die area and improved efficiency in 40nm CMOS

Abstract: Digital transmitters (DTX) have gained interest in the past few years because of their potential to provide compact die area, better efficiency due to the switching nature of the power amplifier core, and scaling with CMOS technology [1][2][3]. Quadrature DTX architecture [1] is favored over polar [3] or outphasing [4] for wideband applications, such as WiFi, because of its ability to scale easily to higher signal bandwidth. Moreover, there is no need for a CORDIC block to convert I/Q signals to amplitude/phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…where R is the average interpolation ratio from t (0) till t h,m . In (18) - (21), it is demonstrated that μ m can yield arbitrary values during the interpolation process. Considering (19) it becomes clear that the major design obstacle for the ASRC is to find an efficient implementation which evaluates the continuous impulse response at arbitrary positions [34], [35].…”
Section: A Sampling Rate Conversionmentioning
confidence: 99%
See 4 more Smart Citations
“…where R is the average interpolation ratio from t (0) till t h,m . In (18) - (21), it is demonstrated that μ m can yield arbitrary values during the interpolation process. Considering (19) it becomes clear that the major design obstacle for the ASRC is to find an efficient implementation which evaluates the continuous impulse response at arbitrary positions [34], [35].…”
Section: A Sampling Rate Conversionmentioning
confidence: 99%
“…11 with 50% LO duty cycle operation is considered. Furthermore, a sharing of the unitary-weighted cells between the I/Q signal components as shown in [21] is assumed. The shared-cell approach is beneficial in order to fully exploit the advantage of the hybrid modulation scheme.…”
Section: Switched-capacitor Rf-dacmentioning
confidence: 99%
See 3 more Smart Citations